(untitled) (Research, Society and Development, 2020)
The aim of the study was to assess the level of functional autonomy and quality of life of physically active older adults. The sample consisted of 13 older adults aged 60-72 years, 12 female and 1 male. Functional Autonomy was assessed using the GDLAM protocol, consisting of C10m, LPS, LPDV, VTC and LCLC tests and the WHOQOL-OLD questionnaire. Participants showed good level of physical activity; however, according to the age classification of the GDLAM protocol group G3 stood out, presenting good classification according to its age group. Regarding quality of life, individuals in general were very satisfied; however, group G1 obtained better score regarding the sensory functioning domain, individuals from G2 stood out, obtaining higher score, and in G3, with only one individual, it was found that the functioning of sensory and past, present and future activities obtained the same score. In conclusion, individuals had "good" functional autonomy index and, regarding quality of life, individuals were in general "very satisfied".